2020
DOI: 10.1159/000513638
|View full text |Cite
|
Sign up to set email alerts
|

Role for Histone Deacetylation in Traumatic Brain Injury-Induced Deficits in Neuropeptide Y in Arcuate Nucleus: Possible Implications in Feeding Behavior

Abstract: Introduction: Repeated traumatic events result in long-lasting neuropsychiatric ailments, including neuroendocrine imbalances. Neuropeptide Y (NPY) in the arcuate nucleus (Arc) is an important orexigenic peptide. However, the molecular underpinnings of its dysregulation owing to traumatic brain injury remain unknown. Methods: Rats were subjected to repeated mild traumatic brain injury (rMTBI) using the closed-head weight drop model. Feeding behaviour and the regulatory epigenetic parameters of NPY expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Earlier studies have reported imbalances in epigenetic marks of DNA methylation and histone acetylation after TBI [ 47 ]. Specifically, both acetylation and methylation of histones are decreased in the brain after CCI injury in rodents [ 2 , 16 , 60 , 75 ]. TBI-induced histone acetylation is caused in part by increases in HDAC activity [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported imbalances in epigenetic marks of DNA methylation and histone acetylation after TBI [ 47 ]. Specifically, both acetylation and methylation of histones are decreased in the brain after CCI injury in rodents [ 2 , 16 , 60 , 75 ]. TBI-induced histone acetylation is caused in part by increases in HDAC activity [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histone hypoacetylation has been observed in murine cortex post-TBI ( Gao et al, 2006 ) and in hippocampus ( Kumari et al, 2023 ). Increased hippocampal histone deacetylase (HDAC) activity has also been observed ( Sagarkar et al, 2019 ) as was neuropeptide Y promoter hypoacetylation ( Balasubramanian et al, 2021b ). TBI was reported to upregulate HDAC2-5 and HDAC11 ( Sagarkar et al, 2019 ) and downregulate HDAC4-5 ( Kamal et al, 2022 ).…”
Section: Epigenetic Modifications Contribute To Tbi Pathologymentioning
confidence: 99%
“…Butyrate depletes MDSC levels in the tumor microenvironment, as part of a wider regulation of tumor microenvironment immune cells and their interactions [ 168 , 169 ]. Butyrate also impacts hypothalamic function, limiting microglia activation and associated hypothalamic inflammation [ 170 ], as well as regulating many hypothalamic and hypothalamic-pituitary fluxes, with immune regulatory consequences [ 171 ].…”
Section: Gut Microbiome Tumor and Mitochondrial Melatonergic Pathwaymentioning
confidence: 99%